Blood Lipids and the Incidence of Atrial Fibrillation: The Multi‐Ethnic Study of Atherosclerosis and the Framingham Heart Study. Issue 5 (7th October 2014) - Alonso, Alvaro; Yin, Xiaoyan; Roetker, Nicholas S.; Magnani, Jared W.; Kronmal, Richard A.; Ellinor, Patrick T.; Chen, Lin Y.; Lubitz, Steven A.; McClelland, Robyn L.; McManus, David D.; Soliman, Elsayed Z.; Huxley, Rachel R.; et al.
Abstract : Background: Dyslipidemia is a major contributor to the development of atherosclerosis and coronary disease. Its role in the etiology of atrial fibrillation (AF) is uncertain. Methods and Results: We studied 7142 men and women from the Multi‐Ethnic Study of Atherosclerosis (MESA) and the Framingham Heart Study who did not have prevalent AF at baseline and were not on lipid‐lowering medications. Total cholesterol, high‐density lipoprotein and low‐density lipoprotein cholesterol, and triglycerides were measured using standard procedures. Incident AF during follow‐up was identified from hospital discharge codes; review of medical charts; study electrocardiograms; and, in MESA only, Medicare claims. Multivariable Cox proportional hazards models were used to estimate hazard ratios and 95% confidence intervals of AF by clinical categories of blood lipids in each cohort. Study‐specific results were meta‐analyzed using inverse of variance weighting. During 9.6 years of mean follow‐up, 480 AF cases were identified. In a combined analysis of multivariable‐adjusted results from both cohorts, high levels of high‐density lipoprotein cholesterol were associated with lower AF risk (hazard ratio 0.64, 95% CI 0.48 to 0.87 in those with levels ≥60 mg/dL versus <40 mg/dL), whereas high triglycerides were associated with higher risk of AF (hazard ratio 1.60, 95% CI 1.25 to 2.05 in those with levels ≥200 mg/dL versus <150 mg/dL). Total cholesterol and low‐density lipoprotein cholesterol were not associated with the risk of AF. Conclusion: In these 2 community‐based cohorts, high‐density lipoprotein cholesterol and triglycerides but not low‐density lipoprotein cholesterol or total cholesterol were associated with the risk of AF, accounting for other cardiometabolic risk factors.